A novel deep eutectic solvent microextraction procedure for enrichment, separation and atomic absorption spectrometric determination of palladium at ultra-trace levels in environmental samples. (1st March 2020) - ALOthman, Zeid A.; Habila, Mohamed A.; Yilmaz, Erkan; Alabdullkarem, Eman A.; Soylak, Mustafa
Highlights: A microextraction procedure has been established for the separation and preconcentration of palledium). The effects of analytical parameters were systematically investigated and optimized. The method has been applied to the analysis of palladium in real samples. Abstract: A dispersive deep eutectic solvent microextraction procedure for the separation and preconcentration of palladium from environmental samples has been established prior to its flame atomic absorption spectrometric determination. The deep eutectic solvent (DES) was prepared by mixing disodium 4, 5-dihydroxy-1, 3-benzenedisulfonate, hydroxyl ammonium chloride, FeCl3 and phenol resulting in homogenous solution which used directly for the extraction of palladium. The analytical parameter including pH, amount of deep eutectic solvent and sample volume were optimized. The developed microextraction procedure was found to have tolerance for the common matrix ions in real samples. The optimization studies resulted in pH was suitable at 6.0 with sample volume up to 35 mL. The preconcentration factor was 116. The detection limit was found as 1.18 µg·L −1 . The presented microextraction method was applied to determination of palladium in marble mine and catalytic converter samples.